Positioning and 'doing' geographies of dissociation. Issue 1 (March 2019) - Ibert, Oliver; Hess, Martin; Kleibert, Jana; Müller, Felix; Power, Dominic
Inspired by five commentaries on our forum article, in this response article we elaborate on three points related to geographies of dissociation, namely positioning dissociation, dealing with plurality and moving from agenda-setting to empirical research. In order to assess the validity of critique elaborated in the commentaries, we specify the contribution we seek to make. Geographies of dissociation aim to contribute to a strand of cultural economic geography that has become increasingly interested in the social construction of symbolic value but that still lacks a conceptual vocabulary for addressing the loopholes and missing links in these relational webs and their related geographies. We explain how geographies of dissociation build on pluralism without ignoring epistemological frictions. Furthermore, we discuss how geographies of dissociation might inspire political economic approaches and future empirical research.